2014
DOI: 10.1007/s00520-014-2499-2
|View full text |Cite
|
Sign up to set email alerts
|

New cutaneous toxicities with generic docetaxel: are the excipients guilty?

Abstract: Our study suggests that some toxic effects of docetaxel may be related to the excipients used in different formulations of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
12
0
2
Order By: Relevance
“…Similarly, a Canadian retrospective study of 364 cases comparing the toxicity between another generic docetaxel and Taxotere, showed less allergic reactions causing treatment discontinuation in the generic group [13]. Another retrospective study of 268 patients in Spain showed significantly fewer grade 3 and 4 HSRs in 2 generic docetaxel formulations compared to Taxotere [14]. Here, we reported the first prospective study to confirm the lower incidence of HSRs in generic docetaxel versus Taxotere.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, a Canadian retrospective study of 364 cases comparing the toxicity between another generic docetaxel and Taxotere, showed less allergic reactions causing treatment discontinuation in the generic group [13]. Another retrospective study of 268 patients in Spain showed significantly fewer grade 3 and 4 HSRs in 2 generic docetaxel formulations compared to Taxotere [14]. Here, we reported the first prospective study to confirm the lower incidence of HSRs in generic docetaxel versus Taxotere.…”
Section: Discussionsupporting
confidence: 55%
“…Unlike in the paclitaxel cohort, the incidences of HSR were significantly different between generic and original docetaxel in this study. The previous retrospective study in Spain showed the lowest HSR incidence in the docetaxel with the lowest polysorbate 80 formulation compared to Taxotere [14]. In our study, Daxotel had the same amount of polysorbate 80 as Taxotere, i.e.…”
Section: Discussionmentioning
confidence: 49%
“…We would like to comment on the paper published by Garrido-Siles et al about the new cutaneous toxicities of generics docetaxel [1]. We had a similar but undocumented experience with docetaxel.…”
Section: Dear Editormentioning
confidence: 89%
“…Esses requisitos legais para produção e comercialização não são suficientes para garantir a intercambialidade e diminuir a desconfiança e as reclamações quanto aos efeitos dos medicamentos genéricos 16 . 18 . Ainda em relação ao Docetaxel, um estudo comparativo entre o produto de referência e três outros produtos genéricos envolvendo 268 pacientes também mostrou diferenças nos riscos relativos de toxicidade dérmica compatíveis com os excipientes utilizados nas diferentes formulações 18 .…”
Section: Os Medicamentos Genéricosunclassified
“…18 . Ainda em relação ao Docetaxel, um estudo comparativo entre o produto de referência e três outros produtos genéricos envolvendo 268 pacientes também mostrou diferenças nos riscos relativos de toxicidade dérmica compatíveis com os excipientes utilizados nas diferentes formulações 18 . Em outro estudo, a comparação entre comprimidos de clopidogrel de três lotes do produto de referência e 18 outros produtos contendo o mesmo fármaco indicou níveis elevados de impurezas nos produtos genéricos.…”
Section: Os Medicamentos Genéricosunclassified